ASSOCIATION OF PHYSICAL ACTIVITY AND DIETARY PATTERNS WITH BLOOD GLUCOSE LEVELS AMONG THE ELDERLY: A CROSS-SECTIONAL STUDY IN KP. MEGAMENDUNG - Saraswasta, I Wayan Gede; Primayanthi, AA Ayu Emi; Ariyanti, Amalia Dewi; Arsyi, Malisadinia (Jurnal Kesehatan Pasak Bumi Kalimantan, 2025)
Background: Hyperglycemia affects approximately 48% of older adults, significantly increasing the risk of cardiovascular disease and stroke. Maintaining optimal blood glucose levels is essential for preserving health and independence in later life. Objective: This study aimed to examine the association between physical activity and dietary patterns with blood glucose levels among elderly individuals. Methods: A quantitative study with a correlational design and cross-sectional approach was conducted involving 32 elderly respondents. The instruments used included the Physical Activity Scale for the Elderly (PASE), adapted from Washburn, and the Food Frequency Questionnaire (FFQ), adapted from Willet. Validity testing showed a significance level of ≤ 0.05 (Sig. 2-tailed), while reliability testing yielded Cronbach’s Alpha values of ≥ 0.801 for the FFQ and 0.813 for the PASE. Results: A majority of participants reported good levels of physical activity (81.3%) and healthy dietary patterns (78.1%), with 68.8% having normal blood glucose levels. Statistical analysis revealed a significant association between physical activity and dietary patterns with blood glucose levels (p-value = 0.015). Conclusion: Improved physical activity and dietary habits are positively associated with more stable blood glucose levels in the elderly. These findings highlight the importance of lifestyle interventions in managing blood glucose and preventing related complications among older adults. Keywords: Physical Activity, Blood Glucose, Dietary Patterns